Hormonal Replacement Treatment for Frozen-Thawed Embryo Transfer With or Without GnRH Agonist Pretreatment: A Retrospective Cohort Study Stratified by Times of Embryo Implantation Failures - Xia, Leizhen; Tian, Lifeng; Zhang, Shanshan; Huang, Jialyu; Wu, Qiongfang (Frontiers in Endocrinology, 2022)
Objective To evaluate the efficacy of the long-acting gonadotropin-releasing hormone agonist (GnRH-a) administration before hormone replacement treatment for frozen-thawed embryo transfer in women with different times of embryo implantation failures. Methods A retrospective cohort study was performed between January 2015 and December 2019. A total of 9263 women who underwent frozen-thawed embryo transfer were included in the study. The study is divided into three parts based on the times of embryo implantation failures. The sample sizes were 4611 for no implantation failure, 3565 for one failure and 1087 for multiple failures. Two endometrium preparation protocols, HRT and HRT with GnRH-a pretreatment (G-HRT), were compared. Confounding factors were treated by propensity score matching and generalized estimation equation. Results For women with no failure of embryo implantation, the live birth rate was not statistically different when they underwent HRT and G-HRT (HRT: 42.75% [498/1165], G-HRT: 45.24% [527/1165], P=0.2261). Similar outcome also appeared in women with one failure of embryo implantation (HRT: 47.22% [535/1133], G-HRT: 50.31% [570/1131], P=0.1413). For women with multiple failures of embryo implantation, the live birth rate was significantly difference (HRT: 38.74% [117/302], G-HRT: 45.48% [357/785], P=0.0449). When stratified by age, the live birth rate is similar for women older than 37 years. Generalized estimation equation showed that GnRH agonist pretreatment was independently associated with the live birth rate for women with multiple failures (adjust OR: 1.5, 95%CI: [1.12-2.00]). Conclusion For women with no/one failure of embryo implantation, the live birth rate is similar between HRT and G-HRT protocols. For women with multiple failure of embryo implantation, GnRH agonist pretreatment is beneficial to raise the live birth rate.